Effusion to the pleural cavity as the clinical manifestation of the relapse of medulloblastoma – the case report - Bernas, Maria; Słomian, Grzegorz; Utracka-Hutka, Beata; Nowara, Elżbieta; Maksymiuk, Beata (Contemporary Oncology/Współczesna Onkologia, 2005)
Medulloblastoma is a rare brain tumor, it affects mainly children and its frequency among adults is less then 1%. Extracranial dissemination is uncommon, but when it happens, the disease spreads to the bones (77%), lymph nodes (33%) and lungs (17%). This can be explained both by anatomical and immunological distinctions of the nervous system and a relatively short overall survival time. In the treatment of medulloblastomas with extracranial dissemination therapeutic benefits may be gained with the use of alkylating agents, alkaloids and cytotoxic antibiotics. This paper presents a case of a 36-year--old male with cerebellar medulloblastoma treated in December 2000 with radical surgery and susequently with adjuvant postoperative radiotherapy. 3 years after initial treatment, the patient had a relaps in the form to dissemination in the thorax and bones (lung, pleura, thoracic vertebrae, sternum and ribs). Main clinical symptoms included shortness of breath caused by pleural effusion and chest pain due to infiltration of intercostals muscles and rib osteolysis. The patient was treated with multidrug chemotherapy based on cisplatin, etoposid and ifosfamid. Before the systemic therapy he received short radiotherapy for the pain of the chest wall. After 6 cycles of chemotherapy, significant regression of the tumor and complete disappearance of symptoms was observed. The only side effect of treatment was anaemia, which required blood substitution and the use of erythropoietin.